MOF-derived sponge-like hierarchical porous carbon for flexible all-solid-state supercapacitors. (18th July 2018) - Cao, Xiao-Man; Sun, Zhi-Jia; Zhao, Si-Yu; Wang, Bing; Han, Zheng-Bo
Abstract : Novel 3D sponge-like hierarchical porous carbons using different-sized MOFs (Zn(tbip) ) as precursors are successfully prepared via a one-step pyrolysis process, and are promising for application in high-performance flexible all-solid-state supercapacitors. Abstract : Novel three-dimensional (3D) interconnected hierarchical sponge-like porous carbons (PCs) using Zn-based MOFs (Zn(tbip) ) with two distinct particle sizes as precursors were prepared via a one-step pyrolysis process. The size effect of the precursor on the porous architecture has been evaluated in detail. The porous carbon derived from small-sizedZn(tbip) at 900 °C (denoted asC-S-900 ) possesses a hierarchical porous structure with the highest specific surface area (1356 m 2 g −1 ), which benefits ion immersion and retention.C-S-900 demonstrates an ultrahigh specific capacitance of 369 and 226 F g −1 at 10 and 400 mV s −1 in a 6 mol L −1 KOH electrolyte, respectively. In addition, a symmetric flexible all-solid-state supercapacitor device was assembled with the electrode ofC-S-900 and PVA/KOH gel electrolyte. The device can offer 96% capacity after 2000 stretching–bending cycles and operate micro-electronic devices displaying excellent mechanical robustness and cycling stability. The present work explored the relationship between the size effect of MOF precursors and the porous carbon architectures to optimize the performance of supercapacitors.